Differentially Expressed MiRNAs and tRNA Genes Affect Host Homeostasis During Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus Infections in Young Pigs - Fleming, Damarius S.; Miller, Laura C. (Frontiers in Genetics, 2019)
Background: Porcine respiratory and reproductive syndrome virus (PRRSV) is a single stranded RNA virus member that infects pigs and causes losses to the commercial industry reaching upwards of a billion dollars annually in combined direct and indirect costs. The virus can be separated into etiologies that contain multiple heterologous low and highly pathogenic strains. Recently the United States has begun to see an increase in heterologous type 2 PRRSV strains of higher virulence (HP-PRRSV). The high pathogenicity of these strains can drastically alter host immune responses and the ability of the animal to maintain homeostasis. Because the loss of host homeostasis can denote underlying changes in gene and regulatory element expression profiles, the study aimed to examine the effect PRRSV infections has on miRNA and tRNA expression and the roles they play in host tolerance or susceptibility. Results: Using transcriptomic analysis of whole blood taken from control and infected pigs at several time points (1, 3, 8 dpi), the analysis returned a total of 149 statistically significant (FDR ⫹ 0.15) miRNAs (n=89) and tRNAs (n=60) that were evaluated for possible pro and anti-viral effects. The tRNA differential expression increased in both magnitude and count as dpi increased, with no statistically significant expression at 1 dpi, but increases at 3 and 8 dpi. The most abundant tRNA amino acid at 3 dpi was alanine, while glycine was the most abundant at 8 dpi. For the miRNAs, focus was put on upregulation that can inhibit gene expression. These results yielded candidates with potential anti and pro-viral actions such as Ssc-miR-125b, which is predicted to limit PRRSV viral levels, and Ssc-miR-145-5p shown to cause alternative macrophage priming. The results also showed that both the tRNAs and miRNAs displayed expression patterns. Conclusions: The results indicated that the HP-PRRSV infection affects host homeostasis through changes in miRNA and tRNA expression and their subsequent gene interactions that target and influence the function of host immune, metabolic, and structural pathways.